2022
DOI: 10.1101/2022.01.29.478314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal membrane proteasomes homeostatically regulate neural circuit activity in vivo and are required for learning-induced behavioral plasticity

Abstract: Protein degradation is critical for brain function through processes that remain poorly understood. Here we investigated the in vivo function of a recently reported neuronal membrane-associated proteasome (NMP) in the brain of Xenopus laevis tadpoles. We demonstrated that NMPs are present in the tadpole brain with biochemistry and electron microscopy, and showed that they actively degrade neuronal activity-induced nascent proteins. Using in vivo calcium imaging in the optic tectum, we showed that acute inhibit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Decreased NSPs may arise by decreasing transcript levels ( Raab-Graham and Niere, 2017 ; Dong et al, 2020 ), for instance, downstream of activity-induced expression of transcriptional repressors ( Ashok et al, 2020 ; Dong et al, 2020 ), by miRNA-mediated mechanisms ( Henshall et al, 2016 ; Bencurova et al, 2021 ; Zolboot et al, 2021 ) or by activity-induced degradation of NSPs. Recent studies identified a neuronal membrane-associated proteosome that degrades activity-induced NSPs ( Ramachandran and Margolis, 2017 ; Ramachandran et al, 2018 ; He et al, 2022 ) and is required for behavioral plasticity ( He et al, 2022 ). Although proteomic analysis of human brain samples indicates that seizure can increase and decrease proteins ( Xiao et al, 2020 ), our data specifically show that activity-induced decreases in NSPs contribute to this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased NSPs may arise by decreasing transcript levels ( Raab-Graham and Niere, 2017 ; Dong et al, 2020 ), for instance, downstream of activity-induced expression of transcriptional repressors ( Ashok et al, 2020 ; Dong et al, 2020 ), by miRNA-mediated mechanisms ( Henshall et al, 2016 ; Bencurova et al, 2021 ; Zolboot et al, 2021 ) or by activity-induced degradation of NSPs. Recent studies identified a neuronal membrane-associated proteosome that degrades activity-induced NSPs ( Ramachandran and Margolis, 2017 ; Ramachandran et al, 2018 ; He et al, 2022 ) and is required for behavioral plasticity ( He et al, 2022 ). Although proteomic analysis of human brain samples indicates that seizure can increase and decrease proteins ( Xiao et al, 2020 ), our data specifically show that activity-induced decreases in NSPs contribute to this outcome.…”
Section: Discussionmentioning
confidence: 99%